Management of human behavior in the organization as a factor of increasing competitiveness - Li Tongyu (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is the processes of managing the work behavior of employees in a company. The subject of research is improving the management of employee behavior in companies and their adaptation during the economic instability caused by war. The purpose of the master's thesis is to develop methodological approaches and practical recommendations for managing employee behavior in a company to enhance its competitiveness. Based on the results of the research, theoretical and practical provisions were formulated. The author developed specific proposals for improving the system for managing employee behavior in companies, focusing on the influence of banking sector trends on human capital management. Scientifically based recommendations obtained through this research can be applied to improve business competitiveness by enhancing employee motivation, fostering a robust corporate culture, and optimizing management processes in conditions of economic instability and crisis. This study underscores the critical importance of managing employee behavior effectively, emphasizing that a welldesigned motivation system and adaptive management strategies are essential for maintaining a competitive edge and achieving sustainable growth.
Scientific advisor: Semenchenko T., PhD in education, associate professor, department management, business and professional communications
Keywords: SOCIAL SCIENCES::Social sciences; management; personnel management; personnel behavior; personnel motivation system; company competitiveness; personnel motivation